The new comedy of Greece and Rome - Hunter, Richard L. 1953- (Cambridge Univ. Press, 1985)
In writing this book on the plays of New Comedy the author's aim is to fill a gap in the existing literature by concentrating on what one might look for in watching and reading these plays and why such an exercise might be pleasurable. The social comedy of Menander, Plautus and Terence provided a style of comic drama which was to prove the root of all subsequent western comedy. Dr Hunter gives a literary account of this drama, placing it in its ancient context and then ranging over a number of specific topics and themes: the dramatic craft of the poets, their exploration of how to give variety to stereotyped plots and characters, the presentation of women, the use of language and themes from tragedy, the place of moralising and philosophy. All Greek and Latin is translated
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Erscheinungsjahr des E-Books: 2011
Keywords: Geschichte 323 v. Chr.-200 v. Chr.; Geschichte 321 v. Chr.-200 v. Chr.; Geschichte 240 v. Chr.-160 v. Chr.; Geschichte 342 v. Chr.-180 v. Chr.; Geschichte 321 v. Chr.-260 v. Chr.; Classical drama (Comedy) / History and criticism; Komödie; Latein; Griechisch